2009
DOI: 10.3390/e11020285
|View full text |Cite
|
Sign up to set email alerts
|

Non-Extensivity of the Configurational Density Distribution in the Classical Microcanonical Ensemble

Abstract: We show that the configurational probability distribution of a classical gas always belongs to the q-exponential family. One of the consequences of this observation is that the thermodynamics of the configurational subsystem is uniquely determined up to a scaling function. As an example we consider a system of non-interacting harmonic oscillators. In this example, the scaling function can be determined from the requirement that in the limit of large systems the microcanonical temperature of the configurational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In a previous paper [21] we have shown that the configurational probability distribution f conf U (q) of an interacting mono-atomic gas with N particles always belongs to the q-exponential family, with…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous paper [21] we have shown that the configurational probability distribution f conf U (q) of an interacting mono-atomic gas with N particles always belongs to the q-exponential family, with…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in [21] that the configurational probability distribution f conf U (q) belongs to the q-exponential family, with…”
Section: The Configurational Subsystemmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the family not only describes phenomena obeying the power-law well [6], but also, it is theoretically proven to include a velocity distribution of the classical gas with N particles [9,10], an attracting invariant manifold of porous media flow [11], and so on. In statistics, it is reported to provide a reasonable statistical model in robust inference from data losing normality [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%